An Extended Theory of Planned Behaviour for Explaining Chinese Domestic Electric Vehicle Purchasing Behaviour - Wang, Zi-Xu; Chee, Wei Ming; Zhang, Qi; Wang, Lei (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
Compared to traditional fuel-powered cars, electric vehicles (EVs) are widely acknowledged as a viable form of transportation and an effective way to address the issues of energy scarcity and air pollution. However, the majority of countries, including China, have recently lowered their preferential treatment and will instead adopt a market-driven strategy to promote EVs. Thus, it is critical to identify the particular elements that support and undermine consumer decisions to choose EVs. This study investigates the impact of perceived value (PV) and consumer ethnocentrism (CE), along with components of TPB, on consumers’ intentions towards the adoption of domestic EVs by using a convenience sample method to collect data. The results showed that attitude, subjective norm (SN), and perceived behavioural control (PBC) positively influence intention. SN positively influences attitude, and attitude plays a mediational role between SN and intention. In addition, PV and CE positively influence attitude towards purchasing domestic EVs. Last, the theoretical and practical implications and limitations are discussed accordingly.